Small business management : (Thomson / South-Western, 2006)
This textbook focuses on the niche occupied by small businesses and its contribution to the larger economy. It introduces the knowledge and skills needed to manage a small business. Chapters address issues of strategy, venture opportunity, marketing, management, and finance. A companion CD-ROM contains tools for creating a business plan, including templates, supporting articles, and video clips. The authors teach at Baylor University.